Association between interleukin-6 gene polymorphisms and febrile seizure risk: A meta-analysis. Issue 39 (September 2019) - Chen, Qingling; Li, Mengmeng; Zhang, Xin; Zhang, Xinyue; Zhong, Rui; Lin, Weihong
Abstract: Background: The association between plasma interleukin-6 (IL-6) levels and the development of febrile seizures (FS) has been reported in multiple previous studies, which showed significantly higher serum IL-6 levels in FS patients than in control patients. However, the mechanism underlying this association remains unclear. One previous study indicated an increased frequency of the −174 GG and −597 GG genotypes in FS patients. Although IL-6 gene polymorphisms may be associated with FS risk, this association remains a matter of debate. Objective: Considering the lack of meta-analyses addressing the possible association between IL-6 gene polymorphisms and the risk of FS, we aimed to perform a meta-analysis to determine the association of IL-6 gene polymorphisms (−572, −174, −597) with the risk of FS. Methods: We conducted a systematic literature search in the PubMed, EMBASE, and WANFANG databases to collect eligible articles. The associations of IL-6 gene polymorphisms with FS risk were evaluated by calculating the pooled odds ratios and 95% confidence intervals. The dominant, recessive, heterozygous, homozygous, and allele genetic models were used to calculate the combined ORs. Results: Our meta-analysis showed that IL-6 (−572, −174, −597) polymorphisms were significantly associated with susceptibility to FS. Conclusion: This study provided knowledge regarding the association of IL-6 (572, 174, 597) polymorphisms with susceptibility to FS. The T allele and TT genotype may be associated with an increased risk for FS.